Exclusive J/ψ and ϒ photoproduction and the low x gluon. (21st January 2016) - Jones, S P; Martin, A D; Ryskin, M G; Teubner, T
Abstract: We study exclusive vector meson photoproduction, with or ϒ, at next-to-leading order (NLO) in collinear factorisation, in order to examine what may be learnt about the gluon distribution at very low x . We examine the factorisation scale dependence of the predictions. We argue that, using knowledge of the NLO corrections, terms enhanced by a large can be reabsorbed in the LO part by a choice of the factorisation scale. (In these exclusive processes ξ takes the role of Bjorken- x .) Then, the scale dependence coming from the remaining NLO contributions has no enhancements. As a result, we find that predictions for the amplitude of ϒ production are stable to within about ±15%. This will allow data for the exclusive process at the Large Hadron Collider (LHC), particularly from LHCb, to be included in global parton analyses to constrain the gluon parton distribution function (PDF) down to Moreover, the study of exclusive photoproduction indicates that the gluon density found in the recent global PDF analyses is too small at low x and low scales.